“They Knock On Our Doors”: Social Representations And Policies On (Im)Migration, From Both Sides Of The Atlantic, Through Online Newspapers - Bocci, Elena; de Rosa, Annamaria Silvana; Negura, Lilian; Latini, Martina; Proietti, Sara; Taieb, Sarah; Masse, Yannick (Psychology Hub, 2023)
Introduction. This study is part of the extension in Canada of a larger program on “Migration Studies” launched in Italy in 2017, inspired by the “modelling” paradigmatic approach to Social Representations Theory. After a short review of the literature, cross-results concerning the transversal analysis of the social media sources in the mother research are briefly presented, in order to contextualize the results presented here. Aims. In this paper we empirically investigate the structure and contents of Social Representations and Policies about (im)migration through the analysis of 2404 articles published online in Canadian and Italian news media (between 2014 and 2020). Hypothesis. Based on the background research results of the mother-research, we expect to find more polarised social representations in Italian articles and less polarized tones in the discussion of immigration in Canadian articles. Methodology. The texts of the articles have been analysed through Descending Hierarchical Classification, using the software IRaMuTeQ. Results. Among the six clusters extracted, four classes refer to the Italian sources and two classes refer to the Canadian ones. This highlights the consistency of the polarised discourse on (im)migration that already emerged from the wider research programme launched in Italy, thus confirming our above-mentioned hypothesis. Study’s limits and possible future developments. Our research is not without limitations. The limitations of the research open up new perspectives for expanding data collection in a spatio-temporal perspective. Impacts of the work. Moving from research to its application value, specific promotional online campaigns could be advocated for by experts in Psychology of Communication, to favour inclusive Policies free of stereotypes and prejudices, expressing positive social representations on (im)migration.